Cross-country differences in the long-run economic impacts of increased fertility - Thomas Davoine (Institut für Höhere Studien - Institute for Advanced Studies (IHS), 2022)
Higher fertility slowly increases the workers-to-retirees ratio over the long run, which can ease the pension financing challenge brought about by population aging. It may or may not increase production per capita. Existing simulation studies all find a positive impact on public finances over the long run. They however differ on the impact on output per capita. Whether differences are due to model designs or country characteristics is unknown. Using the same macroeconomic model for a sample of 14 European countries, I find that the long-run pension deficits are reduced 27% on average, if one woman out of five had one more child in her lifetime. Variations across countries are small. On the other hand, I find that output per capita increases in all countries from my sample, with one exception. Differences in population structures, age-productivity profiles and pension systems can explain the exception. Fertility-promoting policies will always ease the public finance challenge due to population aging, but may worsen output per capita if pension payments are too loosely connected to earnings histories or if age-productivity profiles are very steep.
Keywords: C68; H55; J11; J13; 330; fertility; population aging; pensions; productivity profiles; computable general equilibrium